E-Commerce Shopping Motivation and the Influence of Persuasive Strategies - Adaji, Ifeoma; Oyibo, Kiemute; Vassileva, Julita (Frontiers in Artificial Intelligence, 2020)
Persuasive strategies are used to change the attitude or behavior of people without coercion and are commonly used in online systems such as e-commerce systems. However, in order to make persuasive strategies more effective, research suggests that they should be tailored to groups of similar individuals. The factors that can be used in tailoring persuasive strategies is an ongoing research area. In the present study, we propose the use of shoppers’ online shopping motivation in tailoring six commonly used persuasive strategies: authority, scarcity, commitment, consensus, reciprocity, and liking. We aim to identify how these persuasive strategies can be tailored to e-commerce shoppers based on the consumers’ online shopping motivation. To achieve this, we develop a research model using Partial Least Squares-Structural Equation Modeling (PLS-SEM) and test it by conducting a survey of 226 e-commerce shoppers. The result of our structural model suggests that persuasive strategies influence e-commerce shoppers differently based on their shopping motivation. Balanced buyers - shoppers who typically plan their shopping ahead and are motivated by the need to seek information online - have the strongest influence on commitment strategy and have insignificant effects on the other strategies. Convenience shoppers – those motivated to shop online because of the convenience - have the strongest influence on scarcity, while store oriented shoppers – those who are motivated by the need for social interaction and immediate possession of goods - have the strongest influence on consensus. Variety seekers – consumers who are motivated to shop online because of the opportunity to search through a variety of products and brands, on the other hand, have the strongest influence on authority.